Optical spectroscopy of Nd-doped borate glasses - Padlyak, B. V.; Ryba-Romanowski, W.; Lisiecki, R.; Adamiv, V. T.; Burak, Ya. V.; Teslyuk, I. M. (Видавництво Львівської політехніки, 2012)
Optical absorption, luminescence excitation and emission spectra as well as luminescence kinetics of the Nd3+ centres in glasses with Li2B4O7:Nd, LiCaBO3:Nd, and CaB4O7:Nd compositions containing 0.5 and 1.0 mol. % Nd2O3 have been investigated and analyzed. Using Judd-Ofelt theory oscillator strengths (f) and phenomenological intensity parameters W t ( W 2, W 4, and W 6) for all investigated glasses were determined. Radiative transitions rates (Wr), radiative lifetimes (τrad), and branching ratios (β) for Nd3+ centres have been calculated. Measured lifetimes for Nd3+ centres in the 4F3/2 emitting level are compared with those calculated and quantum efficiency (h) have been estimated.
Keywords: Nd3+-doped borate glasses; optical absorption; Judd-Ofelt analysis; luminescence spectra; decay kinetics